Assessment of outcome of oral supplementation of Vitamin D3 as an adjunct to scaling and root planing in chronic periodontitis patients with type II diabetes mellitus - A randomized controlled clinical trial - G Ramaprabha; Nubesh S Khan; Ramesh Kunusoth; Indrajit Kakati; Syed Shah Hussain Qadri; Pavithra Rangarajan Seshadri (Wolters Kluwer Medknow Publications, 2023)
Background: Both diabetes and periodontitis affect millions of people worldwide and Vitamin D insufficiency may create a conducive environment for the progression of diabetes and periodontal disease. The aim of the study was to assess the outcome of oral supplementation of Vitamin D3 in patients with Type 2Diabetes Mellitus with generalized chronic periodontitis, as an adjuvant toscaling and root planing. Methodology: A total of 92 patients, including 46 each in non-diabetic and diabetec group. Clinical parameters including Plaque Index (PI), Gingival Bleeding Index (GBI), Probing Pocket Depth (PPD), Clinical Attachment Level (CAL), levels of Vitamin D in serum, and Fasting Blood sugar were assessed at the baseline. SRP was finished for each participant in the trial. Following SRP, the first 25people in each group got 60,000 IU of oral vitamin D3 granules once a week for eight weeks, while the remaining 21 subjects from each group did not. At the conclusion of the 8th week following interventions, all the indicators were reviewed. Results: Following SRP and Vitamin D supplementation there was a measurably critical reduction in every one of the periodontal clinical indicators in both groups. In both groups, there was a statistically significant rise in serum vitamin D levels. Conclusion: In addition to SRP, vitamin D supplementation shows promise as a host immunomodulatory drug in the management of periodontitis, particularly in patients with diabetes mellitus.